Psychometric findings and normative values for the CLEFT-Q based on 2434 children and young adult patients with cleft lip and/or palate from 12 countries (2018)
Background: Patients with cleft lip and/or palate can undergo numerous procedures to improve appearance, speech, dentition and hearing. We developed a cleft-specific patient-reported outcome instrument to facilitate rigorous international measurement and benchmarking. Methods: Data were collected from patients aged 8–29 years with cleft lip and/or palate at 30 hospitals in 12 countries between October 2014 and November 2016. Rasch measurement theory analysis was used to refine the scales and to examine reliability and validity. Normative CLEFT-Q values were computed for age, sex and cleft type. Results: Analysis led to the refinement of an eating and drinking checklist and 12 scales measuring appearance (of the face, nose, nostrils, teeth, lips, jaws and cleft lip scar), health-related quality of life (psychological, social, school, speech distress) and speech function. All scales met the requirements of the Rasch model. Analysis to explore differential item functioning by age, sex and country provided evidence to support the use of a common scoring algorithm for each scale for international use. Lower (worse) scores on CLEFT-Q scales were associated with having a speech problem, being unhappy with facial appearance, and needing future cleft-related treatments, providing evidence of construct validity. Normative values for age, sex and cleft type showed poorer outcomes associated with older age, female sex and having a visible cleft. Interpretation: The CLEFT-Q represents a rigorously developed instrument that can be used internationally to collect and compare evidence-based outcomes data from patients aged 8–29 years of age with cleft lip and/or p